On the Moments, Cumulants, and Characteristic Function of the Log-Logistic Distribution - Dian Ekawati; Warsono Warsono; Dian Kurniasari (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2014)
This research examine about the moments, cumulants, and characteristic function of the log-logistic distribution. Therefore, the purposes of this article are (1) finding moments of the log-logistic distribution by using moment generating function and by definition of expected values of the log-logistic random variable and (2) finding the cumulants and characteristic function of the log-logistic distribution. Log-logistic distribution has two parameters: the shape parameter α and β as a parameter scale. Moments of the log-logistic distribution can be determined by using the moment generating function or the definition of expected value. Cumulants determined by the moments that have been found previously. Furthermore, skewness and kurtosis can be determined from the log-logistic distribution. While the characteristic function is the expected value of e^itx, which I as an imaginary number